2009 International Conference on Mechatronics and Automation 2009
DOI: 10.1109/icma.2009.5244909
|View full text |Cite
|
Sign up to set email alerts
|

On the single-zone modeling for optimal climate control of a real-sized livestock stable system

Abstract: This paper discusses mathematical modeling for development and implementation of a model-based optimal indoor climate control for a real-sized livestock stable system. As a typical modern and large-sized stable system, the considered stable uses hybrid ventilation and low-pressure climate control strategies. Due to the main concern of the feasibility for commercializing the developed control system, the single-zone concept is adopted for modeling the considered system. Based on the energy balance and mass bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…where C w is a specific pressure coefficient related to wind direction [13], H out is the equivalent height of the outlet center to the reference pressure level and H npl is the natural pressure level [14].…”
Section: B Inlet and Outlet Throttle Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…where C w is a specific pressure coefficient related to wind direction [13], H out is the equivalent height of the outlet center to the reference pressure level and H npl is the natural pressure level [14].…”
Section: B Inlet and Outlet Throttle Modelsmentioning
confidence: 99%
“…How to effectively reduce buildings' energy consumption and make the operation more environmentally friendly is very crucial for human beings to cope with the climate change and global housewarming. In recent decades, very extensive studies have been focused, from development of efficient buildings [4], [7], mathematical modeling of indoor climate [1], [3], [5], to optimal control of buildings ventilation/Heating Ventilation and Air-Condition (HVAC) systems [8], [13]. Nevertheless, it has been noticed that almost all existing studies only focus on the on-shore situations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows that the energy consumption of buildings accounts up to 40% of energy used worldwide, and buildings lead to 21% of all greenhouse gas emissions [10]. In recent decades, there has been extensive studies on the development of efficient buildings [4], [7], mathematical modeling of indoor climate [1], [3], [5], and optimal control of buildings' ventilation/HVAC systems [8], [12], [13], [14] etc. The literature survey reveals that almost all existing studies on energy-efficient buildings focus on the on-ground situations.…”
Section: Introductionmentioning
confidence: 99%
“…this is very important for offshore systems, from a safety perspective; and • The MPC technique originally rooted and grew up in industrial process applications. Furthermore, some existing investigations [12], [13] for on-ground indoor climate control have indicated that there is a huge potential for using the MPC technique for efficient indoor climate control. It would be quite interesting to check how to extend these results/methods to handle offshore indoor climate situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation